A Proposed Relationship between Time and Load to Quantify Fatigue. (September 2014) - Ahmed, Shaheen; Babski-Reeves, Kari; DuBien, Janice; Webb, Heather
Research has shown that both workload and time are associated with fatigue; however, a functional rela-tionship does not exist. This study observed sixteen participants in their workplace (computer programming and simulation) to quantify the workload-time-fatigue relationship for sedentary tasks. Equal numbers of participants were observed in the morning and afternoon sessions. Workload was measured both subjec-tively and objectively; while fatigue was measured using the Swedish Occupational Fatigue Inventory (SOFI) and a modified Borg scale. Forward selection stepwise regression analysis was performed to deter-mine the underlying mathematical relationship between workload, time, and fatigue. Results indicate that for sedentary tasks, fatigue is a hyperbolic function of workload and time; meaning an inherent interaction-only relationship between workload, time, and fatigue exists. Therefore, an individual can work for longer periods of time if the workload is minimal, and vice versa.